Effect of inhaled prostaglandin E2 on bronchial reactivity to sodium metabisulphite and methacholine in patients with asthma. Issue 9 (September 1991) - Pavord, I D; Wisniewski, A; Mathur, R; Wahedna, I; Knox, A J; Tattersfield, A E
Abstract : Inhaled frusemide protects against the bronchoconstrictor response to a wide range of stimuli that cause bronchoconstriction by indirect mechanisms. One possible explanation for this protection relates to the known ability of frusemide to enhance synthesis of prostaglandin E2 (PGE2). Studies in vitro suggest that PGE2 might protect against indirectly acting bronchoconstrictor challenges rather than those that act directly on airway smooth muscle, though little is known about the effects of PGE2 in vivo. The effect of inhaled PGE2 on the bronchoconstrictor response to inhaled sodium metabisulphite (a stimulus with an indirect action) and methacholine (which acts directly on airway smooth muscle) was studied in nine patients with asthma. Subjects were studied on four days, inhaling PGE2 (100 micrograms) or placebo in a double blind fashion followed immediately by a cumulative dose challenge with sodium metabisulphite or methacholine. The response to the constrictor stimuli was measured as the provocative dose causing a 20% fall in FEV1 (PD20). There was no significant change in FEV1 after inhaled PGE2 compared with placebo, nor any significant change in the response to methacholine; the geometric mean methacholine PD20 was 0.9 mumol after PGE2 and 0.56 mumol after placebo (mean difference 0.7 (95% confidence limits–0.1, 1.5) doubling doses). PGE2, however, protected against sodium metabisulphite, the geometric mean sodium metabisulphite PD20 being 11.8 mumol after PGE2 and 1.8 mumol after placebo (mean difference 2.5 (95% CL 1.9, 3.1) doubling doses). PGE2 conferred significantly greater protection against sodium metabisulphite than methacholine (mean difference 1.8 (95% CL 0.8, 2.8) doubling doses). This suggests that PGE2, like frusemide, has an inhibitory effect on pathways relevant to the bronchoconstriction induced by sodium metabisulphite, with little or no effect on those relevant to methacholine.